Swimmer`s evaluation: technical differences between sprint and middle distance analyzed by inertial sensors - Demarie, S.; Chirico, E.; Vannozzi, G. (Medicina dello Sport, 2022)
BACKGROUND When studying aquatic sports, the direct evaluation during the full and unconstrained swim is difficult as compared to that which is performed on a terrestrial environment. For the cinematic analysis and for the indirect evaluation of the fitness state of the swimmer, inertial sensors have been used, with encouraging results. The aim of this study was to evaluate if through a maximal crawl swimming test with an inertial sensor it is possible to distinguish between the cinematic and technical characteristics of sprint and middle distance swimmers.